E-FILING REPORT: IS PERFORMANCE EXPECTANCY, EFFORT EXPECTANCY, TRUST, AND PERCEIVED RISK INFLUENCING THE INTENTION TO USE THE SYSTEM - Zainavy, Shafa Fadia; Pratama, Bima Cinintya; Fakhruddin, Iwan; Pandansari, Tiara (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2023)
This research was conducted to discover the effect of performance expectancy, effort expectancy, trust, and perceived risk toward intention to use. This research concerns using e-filing as an annual income tax reporting system at the KPP Pratama Purwokerto. This study utilized the population of e-filing users to report annual income taxes by spreading a research questionnaire completed by 200 users. The answers are processed by SMART PLS multiple regression using descriptive statistics, outer model testing (convergent validity, discriminant validity, combined reliability), inner model testing (r-squared, f-squared), and hypothesis testing, suitable methodologies for this study. Multiple regression analysis showed a positive correlation between intention to use, performance expectancy, effort expectancy, and trust. The easiness of the system, accessibility, an impression of trust in the system and the government, and beneficial help for taxpayers in implementing the tax reporting system contribute to the positive effect of performance expectancy, effort expectancy, trust, and perceived risk. Due to the emergence of fear, anxiety, and uncertainty in using the internet and the system as a medium for reporting annual individual tax returns through E-Filing, perceived risk negatively affected the intention to use.